2009
DOI: 10.1080/08995600902768750
|View full text |Cite
|
Sign up to set email alerts
|

Role of Group Affiliation and Gender on Attitudes Toward Women in the Military

Abstract: The current study examined attitudes of West Point cadets (N = 218), Reserve Officer Training Corps (ROTC) cadets (N = 509), and non-military-affiliated students from civilian colleges (N = 598) toward a variety of roles that women may serve in the military. Respondents were queried whether a woman "should" or "should not" serve in the following military jobs: jet fighter pilot, truck mechanic, nurse in a combat zone, typist in the Pentagon, commander of a military installation, handto-hand combat soldier, jet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 8 publications
5
23
0
3
Order By: Relevance
“…It is important to recognize that power differentials embedded in gender relations present within the workplace, including the military [28], can affect women's job performances and overall health and well-being. Servicewomen exposed to violence during their military service have been shown to suffer from poor physical and emotional health [39], are at an increased risk for homelessness [18], and access mental health care services more than servicewomen without histories of violence [37].…”
Section: Resultsmentioning
confidence: 99%
“…It is important to recognize that power differentials embedded in gender relations present within the workplace, including the military [28], can affect women's job performances and overall health and well-being. Servicewomen exposed to violence during their military service have been shown to suffer from poor physical and emotional health [39], are at an increased risk for homelessness [18], and access mental health care services more than servicewomen without histories of violence [37].…”
Section: Resultsmentioning
confidence: 99%
“…Despite equal pay at equal ranks in the military, 13% of women and 2% of men reported they experienced workplace sex discrimination (Lipari et al, 2008). Furthermore, military women are not necessarily viewed as equals by their male colleagues: a recent study found Cadets and ROTC males were less approving than civilian students of women serving in military positions (Matthews, Ender, Laurence, & Rohall, 2009). Understandably, the protective benefit of work is neutralized if the quality of that job is unsatisfactory (Barnett, 2004).…”
Section: Military Environmentmentioning
confidence: 99%
“…Another possible hypothesis is that the military environment may be an indirect contributor to divorce statistics of its female members. Marriage is incentivized in the military and offers enticing benefits at a young age (Matthews, 2009): permission to live off-base as opposed to strict dormitories on-base, and earning more tax-free money through the "with dependents" level of Basic Allowance for Housing (Karney & Crown, 2007;Call & Teachman, 1991). For example, an enlisted member (E-3) in San Antonio, TX, may earn approximately $3528 extra annual allowance for simply being married (Department of Defense, 2009b).…”
Section: Military Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, an estimated 15,450 transgender service members serve in the U.S. armed forces, and there are 134,350 transgender veterans. A 2008 military [29], gays and lesbians in the military [30], and transgender military service [31]. At the precipice of lifting the ban on transgender service, we undertook a qualitative study to gauge the social environment among cisgender cadets and officers regarding open transgender people in the U.S. Army.…”
Section: Introductionmentioning
confidence: 99%